Indonesian Stock Market Reaction to the Quick Count Result of the 2024 Indonesian General Election with an Event Study Approach - Armeldo, Kevin Award (Syntax Corporation, 2025)
The 2024 election in Indonesia will be a moment for the leadership of the President and Vice President to change. Legal certainty may change depending on the leader elected in the next period. Investors attitude has become wait-and-see to see the results of the elections. This study analyzes the impact of the quick count results of the 2024 General Election on the value of shares of companies listed in the LQ45 index on the Indonesia Stock Exchange. The event study method is used with an observation time period of 21 days and 6 days. The variables analyzed were Cumulative Abnormal Return (CAR), Average Trading Volume Activity (ATVA), Day After Quick Count (DAQC), and the effect of Percentage of Foreign Share Ownership (PKSA). The results showed that in the 6-day observation, the quick count results had a significant negative effect on CAR, while PKSA had a significant negative effect on CAR and a significant positive effect on ATVA. In the 21-day observation, there is no significant effect on CAR, but PKSA has a significant positive effect on ATVA despite heteroscedasticity. Short-term investors need to pay attention to the impact of the election quick count results in making investment decisions. However, long-term investors are not affected by the quick election results. Portfolio changes can be made ahead of Election Day to maintain the level of stock price fluctuations.